Genomic surveillance reveals early detection and transition of delta to omicron lineages of SARS-CoV-2 variants in wastewater treatment plants of Pune, India - Rajput, Vinay; Pramanik, Rinka; Malik, Vinita; Yadav, Rakeshkumar; Samson, Rachel; Kadam, Pradnya; Bhalerao, Unnati; Tupekar, Manisha; Deshpande, Dipti; Shah, Priyanki; Shashidhara, L. S.; Boargaonkar, Radhika; et al. (Environmental Science and Pollution Research, 2023)
The COVID-19 pandemic has emphasized the urgency for rapid public health surveillance methods to detect and monitor the transmission of infectious diseases. The wastewater-based epidemiology (WBE) has emerged as a promising tool for proactive analysis and quantification of infectious pathogens within a population before clinical cases emerge. In the present study, we aimed to assess the trend and dynamics of SARS-CoV-2 variants using a longitudinal approach. Our objective included early detection and monitoring of these variants to enhance our understanding of their prevalence and potential impact. To achieve our goals, we conducted real-time quantitative polymerase chain reaction (RT-qPCR) and Illumina sequencing on 442 wastewater (WW) samples collected from 10 sewage treatment plants (STPs) in Pune city, India, spanning from November 2021 to April 2022. Our comprehensive analysis identified 426 distinct lineages representing 17 highly transmissible variants of SARS-CoV-2. Notably, fragments of Omicron variant were detected in WW samples prior to its first clinical detection in Botswana. Furthermore, we observed highly contagious sub-lineages of the Omicron variant, including BA.1 (similar to 28%), BA.1.X (1.0-72%), BA.2 (1.0-18%), BA.2.X (1.0-97.4%) BA.2.12 (0.8-0.25%), BA.2.38 (0.8-1.0%), BA.2.75 (0.01-0.02%), BA.3 (0.09-6.3%), BA.4 (0.24-0.29%), and XBB (0.01-21.83%), with varying prevalence rates. Overall, the present study demonstrated the practicality of WBE in the early detection of SARS-CoV-2 variants, which could help track future outbreaks of SARS-CoV-2. Such approaches could be implicated in monitoring infectious agents before they appear in clinical cases.
Keywords: Bioinformatics pipeline; COVID-19; Early warning; India; Next-generation sequencing; Omicron; Public health; SARS-CoV-2; wastewater; Wastewater-based epidemiology

Tale of two waves: Delineating diverse genomic and transmission landscapes driving the COVID-19 pandemic in Pune, India - Niveditha, Divya; Khan, Soumen; Khilari, Ajinkya; Nadkarni, Sanica; Bhalerao, Unnati; Kadam, Pradnya; Yadav, Ritu; Kanekar, Jugal B.; Shah, Nikita; Likhitkar, Bhagyashree; Sawant, Rutuja; Thakur, Shikha; et al. (Journal of Infection and Public Health, 2023)
Background: Modern response to pandemics, critical for effective public health measures, is shaped by the availability and integration of diverse epidemiological outbreak data. Tracking variants of concern (VOC) is integral to understanding the evolution of SARS-CoV-2 in space and time, both at the local level and global context. This potentially generates actionable information when integrated with epidemiological outbreak data.Methods: A city-wide network of researchers, clinicians, and pathology diagnostic laboratories was formed for genome surveillance of COVID-19 in Pune, India. The genomic landscapes of 10,496 sequenced samples of SARS-CoV-2 driving peaks of infection in Pune between December-2020 to March-2022, were determined. As a modern response to the pandemic, a ``band of five'' outbreak data analytics approach was used. This integrated the genomic data (Band 1) of the virus through molecular phylogenetics with key outbreak data including sample collection dates and case numbers (Band 2), demographics like age and gender (Band 3-4), and geospatial mapping (Band 5).Results: The transmission dynamics of VOCs in 10,496 sequenced samples identified B.1.617.2 (Delta) and BA(x) (Omicron formerly known as B.1.1.529) variants as drivers of the second and third peaks of infection in Pune. Spike Protein mutational profiling during pre and post-Omicron VOCs indicated differential rank ordering of high-frequency mutations in specific domains that increased the charge and binding properties of the protein. Time-resolved phylogenetic analysis of Omicron sub-lineages identified a highly divergent BA.1 from Pune in addition to recombinant X lineages, XZ, XQ, and XM. Conclusions: The band of five outbreak data analytics approach, which integrates five different types of data, highlights the importance of a strong surveillance system with high-quality meta-data for understanding the spatiotemporal evolution of the SARS-CoV-2 genome in Pune. These findings have important implica-tions for pandemic preparedness and could be critical tools for understanding and responding to future outbreaks.& COPY; 2023 Published by Elsevier Ltd on behalf of King Saud Bin Abdulaziz University for Health Sciences. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: COVID-19; Delta; Omicron; SARS-CoV-2 genomic surveillance; Variant of concern; Whole Genome Sequencing (WGS)

Early detection of KP.2 SARS-CoV-2 variant using wastewater-based genomic surveillance in Pune, Maharashtra, India - Rajput, Vinay; Das, Rashmita; Pramanik, Rinka; Nannaware, Kiran; Sushma, Y.; Taji, Nyabom; Rajput, Vishal; Rajkhowa, Riyakshi; Pacharne, Poonam; Shah, Priyanki; Gogate, Niharika; Sangwar, Poornima; et al. (Journal of Travel Medicine, 2024)

Immunogenicity of SARS-CoV-2 vaccines BBV152 (COVAXIN®) and ChAdOx1 nCoV-19 (COVISHIELD™) in seronegative and seropositive individuals in India: a multicentre, nonrandomised observational study - Asokan, Mangaiarkarasi S.; Joan, Roshni Florina; Babji, Sudhir; Dayma, Girish; Nadukkandy, Prajitha; Subrahmanyam, Vinutha; Pandey, Archana; Malagi, Girish; Arya, Pooja; Mahajan, Vibhuti; Bhavikatti, Jayateerth; Pawar, Ketakee; et al. (Lancet Regional Health - Southeast Asia, 2024)
<p style="box-sizing: inherit; line-height: 1.5; margin: 1.2rem 0px; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px;"> Background: There are limited global data on head-to-head comparisons of vaccine platforms assessing both humoral and cellular immune responses, stratified by pre-vaccination serostatus. The COVID-19 vaccination drive for the Indian population in the age group 18-45 years began in April 2021 when seropositivity rates in the general population were rising due to the delta wave of COVID-19 pandemic during April-May 2021. <p style="box-sizing: inherit; line-height: 1.5; margin: 1.2rem 0px; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px;"> Methods: Between June 30, 2021, and Jan 28, 2022, we enrolled 691 participants in the age group 18-45 years across four clinical sites in India. In this non-randomised and laboratory blinded study, participants received either two doses of Covaxin® (4 weeks apart) or two doses of Covishield™ (12 weeks apart) as per the national vaccination policy. The primary outcome was the seroconversion rate and the geometric mean titre (GMT) of antibodies against the SARS-CoV-2 spike and nucleocapsid proteins post two doses. The secondary outcome was the frequency of cellular immune responses pre- and post-vaccination. <p style="box-sizing: inherit; line-height: 1.5; margin: 1.2rem 0px; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px;"> Findings: When compared to pre-vaccination baseline, both vaccines elicited statistically significant seroconversion and binding antibody levels in both seronegative and seropositive individuals. In the per-protocol cohort, Covishield™ elicited higher antibody responses than Covaxin® as measured by seroconversion rate (98.3% vs 74.4%, p < 0.0001 in seronegative individuals; 91.7% vs 66.9%, p < 0.0001 in seropositive individuals) as well as by anti-spike antibody levels against the ancestral strain (GMT 1272.1 vs 75.4 binding antibody units/ml [BAU/ml], p < 0.0001 in seronegative individuals; 2089.07 vs 585.7 BAU/ml, p < 0.0001 in seropositive individuals). As participants at all clinical sites were not recruited at the same time, site-specific immunogenicity was impacted by the timing of vaccination relative to the delta and omicron waves. Surrogate neutralising antibody responses against variants-of-concern including delta and omicron was higher in Covishield™ recipients than in Covaxin® recipients; and in seropositive than in seronegative individuals after both vaccination and asymptomatic infection (omicron variant). T cell responses are reported from only one of the four site cohorts where the vaccination schedule preceded the omicron wave. In seronegative individuals, Covishield™ elicited both CD4+ and CD8+ spike-specific cytokine-producing T cells whereas Covaxin® elicited mainly CD4+ spike-specific T cells. Neither vaccine showed significant post-vaccination expansion of spike-specific T cells in seropositive individuals.

Long-term genomic surveillance of SARS-CoV-2 in campus wastewater depicts lineage trends and public health implications during and after omicron waves - Pramanik, Rinka; Rajput, Vinay; Malik, Vinita; Nannaware, Kiran; Matra, Sejal; Joshi, Sai; Kumar, Shubham; Samson, Rachel; Yadav, Rakesh Kumar; Shah, Priyanki; Shashidhara, LS; Dastager, Syed; et al. (Environment & Health, 2025)
SARS-CoV-2 transmission and detection on academic campuses in low- to middle-income countries has not been explored. The present study explored wastewater surveillance of SARS-CoV-2 in a campus setting in Pune, Maharashtra, India, offering insights into variant-specific trends and their correlation with clinical cases over a 2.5 year period from November 2021 to April 2024. We collected 242 wastewater samples from the campus sewershed and processed them to extract RNA and perform RT-qPCR and sequencing, followed by lineage assignment using the LCS tool. Early signals of different SARS-CoV-2 variants, such as BA.2.X, JN.1.X, and KP.2.X, were detected in wastewater prior to its first clinical report in Maharashtra, India. Wastewater viral load strongly correlated with clinical cases during the Omicron phase (ρ = 0.73–0.81) compared to the post-Omicron phase (ρ = −0.06 to 0.31). This study also highlights that alerts and warnings issued on the basis of wastewater viral hikes have proven instrumental in preventing outbreaks of SARS-CoV-2 variants on campus. However, downgrading COVID-19 from pandemic status by the WHO resulted in a subsequent decrease in public vigilance, changing the viral dynamic in the last phase of the study. This study showcases the utility of wastewater surveillance in a campus setting as an early warning system and understands the interplay of public health policy effects in viral dynamics within controlled ecosystems, such as campuses or offices.

Monitoring influenza A (H1N1, H3N2), RSV, and SARS-CoV-2 using wastewater-based epidemiology: A 2-year longitudinal study in an Indian megacity covering omicron and post-omicron phases - Pramanik, Rinka; Nannaware, Kiran; Malik, Vinita; Shah, Priyanki; Sangewar, Poornima; Gogate, Niharika; Shashidhara, L. S.; Boargaonkar, Radhika; Patil, Dhawal; Kale, Saurabh; Bhalerao, Asim; Jain, Nidhi; et al. (Food and Environmental Virology, 2025)
{The bourgeoning field of wastewater-based epidemiology (WBE) for the surveillance of several respiratory viruses which includes Influenza A, H1N1pdm09, H3N2, respiratory syncytial viruses (RSV), and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is of interest for public health concerns. However, there are few long-term monitoring studies globally. In this study, respiratory viruses were detected and quantified from 11 sewer sheds by utilizing reverse transcription-quantitative polymerase chain reaction analysis in Pune city, India, from Jan 2022 to Dec 2023. The RNA fragments of respiratory viruses were detected in sewage samples before clinical cases were reported, underscoring the potential of WBE for early detection and monitoring within the population. The Spearman correlation of wastewater viral copies was positively and significantly correlated with the clinically positive case of H1N1pdm09 (rho = 0.55
Keywords: Influenza A; Quantitative reverse transcription-PCR; Respiratory viruses; SARS-CoV-2; Wastewater-based epidemiology